1994
DOI: 10.1177/026553229401100104
|View full text |Cite
|
Sign up to set email alerts
|

The effects of note-taking on listening comprehension in the Test of English as a Foreign Language

Abstract: This study examined the effects of taking notes in the portion of the TOEFL listening comprehension section that contains short monologues, or 'mini talks'. These effects were assessed in experimental testing sessions with students in intensive English language programmes and with undergraduate and graduate international students. A multiple-choice questionnaire sur veyed the students' reactions to the opportunity to take notes and their previous note-taking experiences. Allowing students to take notes had li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 14 publications
1
22
1
1
Order By: Relevance
“…However,the author pointed out that requiring the participants to take notes (as this was the source of the dependent measure) may have interfered with their comprehension of both passages, preventing the discovery of an advantage for the familiar structure. This is in line with the findings of Hale and Courtney (1994), who found that participants compelled to take notes actually showed inferior listening comprehension relative to when they were not allowed to take notes at all (see section below on Note-Taking).…”
Section: Rhetorical Structuresupporting
confidence: 90%
See 3 more Smart Citations
“…However,the author pointed out that requiring the participants to take notes (as this was the source of the dependent measure) may have interfered with their comprehension of both passages, preventing the discovery of an advantage for the familiar structure. This is in line with the findings of Hale and Courtney (1994), who found that participants compelled to take notes actually showed inferior listening comprehension relative to when they were not allowed to take notes at all (see section below on Note-Taking).…”
Section: Rhetorical Structuresupporting
confidence: 90%
“…As always, however, it is difficult to interpret a null effect. What can be concluded from Hale and Courtney's (1994) study is that urging L2 listeners to take notes can hurt their comprehension test performance.…”
Section: Note Taking In the L2mentioning
confidence: 91%
See 2 more Smart Citations
“…Some studies investigating the relationship between note-taking (as opposed to no note-taking) and listening comprehension resulted in no significant relationship between the two (Dunkel, 1988;Hale & Courtney, 1994;Chaudron, Loschky, & Cook, 1994).…”
Section: Review Of Literaturementioning
confidence: 99%